2011
DOI: 10.1152/jn.00312.2011
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes promote peripheral nerve injury-induced reactive synaptogenesis in the neonatal CNS

Abstract: Lo F-S, Zhao S, Erzurumlu RS. Astrocytes promote peripheral nerve injury-induced reactive synaptogenesis in the neonatal CNS. J Neurophysiol 106: 2876 -2887. First published September 7, 2011 doi:10.1152/jn.00312.2011.-Neonatal damage to the trigeminal nerve leads to "reactive synaptogenesis" in the brain stem sensory trigeminal nuclei. In vitro models of brain injury-induced synaptogenesis have implicated an important role for astrocytes. In this study we tested the role of astrocyte function in reactive syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 82 publications
0
37
0
Order By: Relevance
“…Future studies will more directly examine whether the effects of GBP reported here are due to interruption of TSP/α2δ-1 signaling. Although the mechanism for these effects remains uncertain, changes in TSP/α2δ-1-driven excitatory synaptogenesis have been suggested to mediate the therapeutic effects of GBP in several injury models (Li et al, 2012; Lo et al, 2011) and may play a role in the protective effects of GBP in the FL cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies will more directly examine whether the effects of GBP reported here are due to interruption of TSP/α2δ-1 signaling. Although the mechanism for these effects remains uncertain, changes in TSP/α2δ-1-driven excitatory synaptogenesis have been suggested to mediate the therapeutic effects of GBP in several injury models (Li et al, 2012; Lo et al, 2011) and may play a role in the protective effects of GBP in the FL cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, its therapeutic actions appear to be mediated by antagonizing the interaction of TSP and α2δ-1 (Eroglu et al, 2009; Eroglu, 2009). Recent studies have shown that GBP treatment prevented injury-induced increases in reactive astrocytosis and excitatory synaptogenesis (Li et al, 2012; Lo et al, 2011). Furthermore, GBP treatment attenuated cortical hyperexcitability in a model of posttraumatic epilepsy associated with upregulation of α2δ-1 (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new silent synapses were found in the adult brain after exposure to cocaine (Huang et al, 2009;Koya et al, 2012), trauma (Lo et al, 2011), chronic stress (Suvrathan et al, 2014), or during aging (Sametsky et al, 2010). Their formation involves de novo synaptogenesis and (or) removal of AMPAR from regular synapses (Hanse et al, 2013).…”
Section: Formation and Role Of Silent Synapsesmentioning
confidence: 99%
“…Although increases in synapse number are observed in the dorsal horn in neuropathic pain states (Jaken et al, 2010; Lin et al, 2011; Peng et al, 2010), the spinal signals initiating synaptogenesis remain unclear. One family of extracellular matrix proteins, the thrombospondins (TSPs), promotes synaptogenesis (Christopherson et al, 2005; Eroglu et al, 2009; Lo et al, 2011). The thrombospondins are glycoproteins that are produced by numerous cell types and have widely varying roles in cell signaling (Adams, 2001; Adams and Lawler, 2004).…”
Section: Introductionmentioning
confidence: 99%